PERSEPSI MAHASISWA BIDIKMISI UNIVERSITAS DIPONEGORO TERHADAP HARAPAN MASA DEPANNYA - Eva Nurlaily Rohmah; Warsito .; Turtiantoro . (Journal of Politic and Government Studies, 2015)
ABSTRACTThe Poverty is still a fundamental problem that must be faced by the Indonesiangovernment. One of the effects of poverty is the low level of public education. Therefore,to break the vicious circle of poverty, the government develop policies of education byproviding scholarships to students who have good academic potential and theeconomically disadvantaged, the program is a program Bidikmisi (Beasiswa PendidikanBagi Mahasiswa Berprestasi). The Bidikmisi scholarships as government policies that canmotivate people to compete in a weak economy seize the opportunity to continue theireducation at the famous State University in hopes of changing the future. It raises thepublic perception of bidikmisi education policy in realizing his future hopes. Therefore,the problem in this research is